Unit Commitment Using Embedded Systems. (2015) - Jayabarathi, R.; Jisma, M.; Suyampulingam, A.
Abstract: Unit commitment problem helps in deciding which electricity generation unit should be running in each period so as to satisfy a predictably varying demand for electricity. Unit Commitment enables uninterruptible power to be delivered to consumers using the principle of minimum operating cost. In this paper a laboratory prototype for unit commitment is developed using embedded systems. In this work, the unit commitment problem is solved using dynamic programming approach. The generators are switched ON and OFF on a priority basis to minimize the total operating cost of the generating units. An Embedded Development Kit(EDK) is used for the prototype which supports micro framework technology. The laboratory prototype is tested for various combinations of generating units.